Influence of maximum applied shear rate on the measured rheological properties of flowable cement pastes. (March 2019) - Feys, Dimitri; Asghari, Azadehalsadat
Abstract: Rheological properties of cement-based materials have been widely studied over the last decades. These materials show a yield stress and viscosity, which change over time due to thixotropic behavior and the hydration reaction. The consequence of thixotropy is that the rheological properties are dependent on the applied shear rate, time and temperature. This paper describes the change in rheological properties of well-dispersed cement pastes subjected to different shear rates. It is shown that a majority of the structural breakdown occurs when transitioning from rest to a low shear rate, but a number of connections can only be broken at more elevated shear rates. As a result, especially the viscosity decreases with increasing applied shear rate. The influence of temperature, binder composition and choice of chemical admixtures on the change in rheological properties with applied shear rate is evaluated in this paper.